Benfluorex and unexplained valvular heart disease: a case-control study. - Irène Frachon (Public Library of Science (PLoS), 2010)
Background Recent case reports suggest that benfluorex, a fenfluramine derivative used in the management of overweight diabetic patients and dyslipidemia, is associated with cardiac valve regurgitation. Methods We conducted a case-control study. Eligible patients were those admitted in the cardiology or the cardiac surgery units of our hospital between January, 1(st) 2003 and June 30(th) 2009, with mitral insufficiency diagnostic codes (ICD-10 I340 and I051). Patients with either a primary cause (degenerative, known rheumatic heart disease, infectious endocarditis, congenital, radiation-induced valvular disease, associated connective and/or vasculitis disease, trauma, tumor) or a secondary (functional) cause were considered as having an "explained" mitral regurgitation. Other patients were considered as having an "unexplained" mitral regurgitation and were included as cases. For each case, two controls were matched for gender and for the closest date of birth, among a list of patients with an "explained" mitral regurgitation. Drug exposures were assessed blindly regarding the case or control status, through contacts with patients, their family and/or their physicians. Results Out of the 682 eligible patients, 27 cases and 54 matched controls were identified. The use of benfluorex was reported in 22 patients: 19 of the 27 cases, versus 3 of the 54 controls, odds-ratio 17.1 (3.5 to 83), adjusted for body mass index, diabetes and dexfenfluramine use. Conclusion The use of benfluorex is associated with unexplained mitral regurgitation.